MAGNETOTELURIC AND MAGNETOVARIATE RESEARCHES IN THE ENDOCONTACT AREA OF KORNINSKY GRANITE ARRAY - Ilyenko, V.; Burakhovich, T.; Kushnir, A.; Popov, S.; Omelchuk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In 2018-2019, work was carried out to study the deep geoelectric structure of a complex system of intersection of the sub-latitudinal zone between the Andrushevsky and Masherinsky faults and the sub-meridional between Brusilovsky and Olshansky. Plane synchronous observations of the lowfrequency natural electromagnetic field of the Earth of ionospheric-magnetospheric origin in a wide range of periods are made. The transmission operators of MT/MV fields were evaluated using the PRC-MTMV software package. The obtained tipper estimates for periods of geomagnetic variations from 50 to 3100 s, curves of apparent resistance and impedance phases from 20 to 10000 s. According to the interpretation of the results of magnetotelluric studies, the Brusilovsky deep fault in the form of a subvertical surface lowresistance anomaly was clearly recorded. Analyzing these and previous works, it can be stated that within the Volyn megablock Ukrainian shield, the Brusilovsky deep fault is manifested by an anomalous highly conductive structure from the surface. Within the framework of the Rosinsky megablock, the Brusilov fault zone is not completely anomalous, and only its individual components (Velikoerchik fault) are anomalous, its conductivity decreases almost four times. The western border of the Korninsky massif is less clearly distinguished, as the relatively electrically conductive from the surface, which is most likely associated with the surface conductivity of minor sedimentary deposits or fracturing of rocks in the crystalline basement. It should also be emphasized that on pseudo-sections of magnetotelluric parameters, the SUS point (picket 14 km) did not appear to be anomalous, but the behavior of the curves for different polarizations, and especially low magnetovariational characteristics, may indicate that the deep structure of the region must be classified as heterogeneous. Moreover, this point is located near the zone of metasomatically altered rocks and multidirectional faults of low rank. One explanation of this may be that the processes of secondary changes in granitoids do not lead to an increase in porosity, the solutions which are filtered are immediately saturated with calcium and alkalis, filling the fluid flow paths.